The aesthetic experience with the didactic use of cinema in Philosophy classes: a perspective from John Dewey (Revista Apotheke, 2025)
This article explores the aesthetic experience provided by the use of cinema as a didactic resource in Philosophy classes, based on John Dewey’s ideas about art and education. Drawing on his main works, such as Art as Experience and Democracy and Education, we observe that Dewey calls our attention to the realization that the real meaning that an aesthetic attitude can provide concerns a disinterested attitude, an openness, a readiness not so much for the thing or event “in itself,” in its consistency, but for the effects it can produce, so that the idea of art has expanded and surpassed the limits of intelligibility. Thus, the contribution of Deweyan thought is directed towards the perspective of an enrichment of such experiences and, therefore, under a formative prism. Obviously, the challenge lies in developing fruitfully, at the core of high school education, as is the focus of our work, the provocations that may arise from different artistic expressions. The work of art has always served as an object of philosophical reflection, achieving an active position as a transforming agent in philosophical questions. This is confirmed when, in the current context, aspects such as consumerism, unbridled competition, difficulty in living with plurality and differences, separation between art and life, fragmentation and commodification of human relations, among others, express themselves as reflections of the dualisms that markedly affect human life. For this reason, the work Art as Experience has an extremely current reach to, through the bias of aesthetic experience and the postulate of unity between art and life, think about these and other issues that affect the life of contemporary man. In a special way, we can analyze how cinema in different productions has reproduced distinct ways of thinking about the philosophical problem that affects us in its great majority, the educational model and the school environment.
Keywords: cinema; Dewey; education; philosophy teaching; aesthetic experience